(untitled) (Revista Española de Fisiología, 1988)
Glomerular filtration rate, urine volume, sodium excretion and mean arterial pressure were measured in 10 rats with Cl4C induced cirrhosis presenting sodium retention and ascites, and in 10 control rats before and during the iv administration of the 28 aminoacid rat alpha-Atrial Natriuretic Peptide (alpha-ANP) (a bolus of 1 microgram followed by a constant infusion of 33 ng/min).alpha-ANP induced a similar increase in glomerular filtration rate and filtered sodium load in both groups of rats.In contrast, the increase in urine volume and sodium excretion produced by alpha-ANP was significantly lower in cirrhotic rats (from 13.8 +/- 1.9 to 37.9 +/- 9.1 microliters/min., and from 0.5 +/- 0.1 to 3.3 +/- 1.0 microEq/min) than in control animals (from 14.6 +/- 1.3 to 102.5 +/- 17.7 microliters/min., p less than 0.005; and from 1.0 +/- 0.3 to 14.1 +/- 3.2 microEq/min., p less than 0.001).The results indicate that in rats with experimental cirrhosis and ascites there are blunted diuretic and natriuretic responses to alpha-ANP, probably as a consequence of the exaggerated tubular sodium reabsorption present in these animals.